#### Answer

$$18, \quad -5.$$

#### Work Step by Step

Since $ f(x,y)=x+yx^3$, then
$$ f(2,2)=2+(2)(2)^3=2+16=18.$$
$$ f(-1,4)=-1+4(-1)^3=-1-4=-5.$$

Chegg costs money, GradeSaver solutions are free!

Published by
W. H. Freeman

ISBN 10:
1464125260

ISBN 13:
978-1-46412-526-3

$$18, \quad -5.$$

Since $ f(x,y)=x+yx^3$, then
$$ f(2,2)=2+(2)(2)^3=2+16=18.$$
$$ f(-1,4)=-1+4(-1)^3=-1-4=-5.$$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.